2015
DOI: 10.3899/jrheum.140543
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Immunoglobulin Free Light Chains During the Preclinical Period of Rheumatoid Arthritis

Abstract: Objective Immunoglobulin free light chains (FLCs) represent biomarkers of B-cell activity in rheumatoid arthritis (RA) and are associated with all-cause mortality in the general population. Our objective was to evaluate the relationships of serum FLCs to pre-clinical disease, RA characteristics, and mortality in RA compared to non-RA subjects. Methods A population-based study in Olmsted County, Minnesota, was performed by cross-linking a large cohort in the general population having available serum FLC measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…FLCs are important for diagnosing, monitoring and prognosticating multiple myeloma, monoclonal gammopathy of unknown significance (MGUS) and an array of other associated disorders [1]. More recently, the prognostic utility of FLCs in non-neoplastic disorders has been highlighted [2][3][4]. Moreover, the sum of polyclonal κ and λ FLCs, expressed as ∑FLC, has been advocated as a global biomarker of immune activation [5], and is now regarded as a powerful prognostic marker for overall survival in the general population [6].…”
Section: Introductionmentioning
confidence: 99%
“…FLCs are important for diagnosing, monitoring and prognosticating multiple myeloma, monoclonal gammopathy of unknown significance (MGUS) and an array of other associated disorders [1]. More recently, the prognostic utility of FLCs in non-neoplastic disorders has been highlighted [2][3][4]. Moreover, the sum of polyclonal κ and λ FLCs, expressed as ∑FLC, has been advocated as a global biomarker of immune activation [5], and is now regarded as a powerful prognostic marker for overall survival in the general population [6].…”
Section: Introductionmentioning
confidence: 99%
“…Down‐regulation of neutrophil apoptotic genes is demonstrated in PD and long established in RA plausibly contributing to prolonged inflammation . Immunoglobulin production and IgG titers are higher in RA, even in the pre‐arthritic phase, being associated with autoantibody production . Severe periodontitis‐affected RA subjects have shown greater anti P. gingivalis IgG and IgM, while emerging evidence also shows heightened immunoglobulin response in RA to the pathobiont P. copri .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation was only assessed using a single biomarker, sFLCs, which are produced directly by activated B cells. Although, sFLCs are clinically useful in rheumatoid arthritis, [17][18][19][20] distinct inflammatory pathway to other inflammatory measures, such as CRP. 30…”
Section: Limitations Of Our Studymentioning
confidence: 99%
“…Serum‐free light chains (sFLCs) are inflammatory markers produced by immune cells of plasma cell lineage, they are renally cleared with a half‐life of 2–5 h. Initial studies have demonstrated the potential of sFLCs as a clinically useful biomarker across various fields . In rheumatoid arthritis, sFLC concentrations correlate with disease activity, and sFLC concentrations are raised 3–5 years before the clinical diagnosis of rheumatoid arthritis . The role of sFLCs has not yet been investigated in FAI or osteoarthritis.…”
mentioning
confidence: 99%
See 1 more Smart Citation